Simon Elliott, Ancient Greeks at War: Warfare in the Classical World from Agamemnon to Alexander. - Dickinson, Oliver (Journal of Greek Archaeology, 2022)
Simon Elliott, Ancient Greeks at War: Warfare in the Classical World from Agamemnon to Alexander. pp. 288, with 134 col. ills, 8 double-page col. maps, 5 col. battle-plans. Oxford & Philadelphia: Casemate Publishers, 2021. ISBN 978-1-61200-998-8, hardback £30; 978-1-61200-999-5, E-book £12.99.